Rapid Detection of Toxic Dinofl agellate, Alexandrium minutum (Dinophyceae) Using Fluorescence In Situ Hybridization (FISH) - Yek, Leh-Hie; Hii, Kieng-Soon; Tan, Toh-Hii; Kon, Nyuk-Fong; Lim, Po-Teen; Leaw, Chui-Pin (Malaysian Journal of Science, 2013)
Harmful algal blooms (HABs) are phenomena known as sudden increase in Microalgal population that cause seafood poisoning in human and impact to marine ecosystem. Dinofl agellates from the genus Alexandrium had been known to be responsible for paralytic shellfi sh poisoning (PSP) toxins with the production of sodium blocking neurotoxins collectively called saxitoxin (STX). Species identifi cation in thisgenus is based on thecal plate tabulation and minute morphological character, which is often hard to observe during regular plankton monitoring that require taxonomic expertise. Hence, a molecular detection approach using whole-cell fl uorescence in situ hybridization (FISH) was investigated in this study for the rapid detection of Alexandrium. Ribosomal DNA probes targeting the toxic A.minutum were designed in silico. Specifi city and accessibility of designed probes were further verifi ed in silico by comparing parameters that infl uenced hybridization kinetics. Species-specifi c probe which was designated as L-S-Amin-569-A-18 was synthesized and optimized using the clonal cultures of A. minutum. The results showed that the DNA probe had high specifi city towards A. minutum, with no cross-reactivity towards other Alexandrium species. The whole-cell FISH coupled with the speciesspecifi c probe showed its potency as a rapid detection tool of A. minutum in Malaysian waters,which could be adopted in the national harmful algal monitoring program. (Keywords: Paralytic shellfi sh poisoning (PSP); Alexandrium minutum, â€œfl uorescence in situ hybridizationâ€ (FISH);DNA probe)